The Proresolving Lipid Mediator Maresin1 Alleviates Experimental Pancreatitis via Switching Macrophage Polarization - Yingying Lu; Guotao Lu; Lin Gao; Qingtian Zhu; Jing Xue; Jingzhu Zhang; Xiaojie Ma; Nan Ma; Qi Yang; Jie Dong; Weijuan Gong; Weiqin Li; et al. (Mediators of Inflammation)
Background and Purpose. Previous studies showed that Maresin1 (MaR1), one of the metabolites from docosahexaenoic acid (DHA), could alleviate acute inflammation and prompt inflammation resolution. Also, it attenuated pancreatic injury in caerulein-induced acute pancreatitis (AP) in mice. However, the mechanisms underlying this suppression of inflammation and AP remain unknown. Method. Repeated caerulein injection was used to induce AP and chronic pancreatitis (CP) models in mice. The histopathological and serological changes were examined for evaluating the severity of the AP model, and flow cytometry was used for detecting macrophage phagocytosis and phenotype. Meanwhile, clodronate liposomes were used for macrophage depletion in mice. Finally, the CP model was adopted to further observe the protective effect of MaR1. Result. MaR1 administration manifested the improved histopathological changes and the lower serum levels of amylase and lipase. However, MaR1 played no protective role in the pancreatic acinar cell line in vitro. It obviously reduced the macrophage infiltration in the injured pancreas, especially M1-type macrophages. After macrophage clearance, MaR1 showed no further protection in vivo. This study also demonstrated that MaR1 could alleviate fibrosis to limit AP progression in the CP model. Conclusion. Our data suggests that MaR1 was a therapeutic and preventive target for AP in mice, likely operating through its effects on decreased macrophage infiltration and phenotype switch.